Diabetic Retinopathy: Pathophysiology and Modern Therapeutic Strategies - Wiekiera, Adrianna; Wiekiera , Mateusz; Kopciał, Szymon; Budzik, Paweł; Kornatowska, Karolina; Rataj, Jonatan (Quality in Sport, 2026)
Diabetic retinopathy (DR) is one of the most common and serious chronic complications of diabetes mellitus, representing the leading cause of vision loss among working-age adults. The disease results from prolonged hyperglycemia, which leads to damage of the retinal microvasculature, causing endothelial dysfunction, increased vascular permeability, ischemia, and subsequent pathological neovascularization. Two main stages of DR are distinguished — non-proliferative (NPDR) and proliferative (PDR) — reflecting the progressive severity of vascular alterations within the retina. Early stages of the disease are often asymptomatic, making regular ophthalmic screening and advanced imaging techniques, such as optical coherence tomography (OCT) and fluorescein angiography, essential for early detection. Management of diabetic retinopathy includes both systemic metabolic control (maintaining optimal blood glucose, blood pressure, and lipid levels) and local treatments, such as laser photocoagulation, intravitreal injections of VEGF inhibitors or corticosteroids. In advanced cases, vitrectomy may be required. Despite significant progress in diagnosis and therapy, DR remains a major public health concern, requiring close collaboration between diabetologists, ophthalmologists, and patients. This review summarizes the current understanding of the pathogenesis, classification, diagnostic methods, and treatment strategies for diabetic retinopathy, with particular emphasis on recent research directions and potential innovative therapeutic approaches.